(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La tutela della salute nell’emergenza sanitaria: le raccomandazioni e linee guida delle società scientifiche quali sintomi della crisi delle fonti del diritto - 3. Il concetto di vulnerabilità - 4. Le Raccomandazioni di etica clinica della SIAARTI del 6 marzo 2020: criticità - 5. Le linee guida SIAARTI-SIMLA: nulla di nuovo nelle scelte di triage – 6. Conclusioni. The problem of vulnerability in the SIAARTI Recommendations and in the SIAARTI-SIMLA guidelines ABSTRACT: During the health emergency from Covid-19 a situation of scarcity of health resources has been realized that has induced the SIAARTI to elaborate of the recommendations of clinical ethics. The latter are subject to multiple criticism because of the choice of criteria for allocation of resources because one of the criteria used is the chronological criteria. From this it was decided to analyze the condition of a category of vulnerable people, namely the elderly, during the health emergency. Subsequently, the position these subjects possess within the recommendations of clinical ethics of SIAARTI and the guidelines elaborated by SIAARTI and SIMLA was analyzed.